Single‐session multiple stent deployment using moving cell stent without dilating initial stent mesh to treat malignant hilar biliary obstruction (with videos). (13th November 2019) - Ogura, Takeshi; Takenaka, Mamoru; Shiomi, Hideyuki; Nishioka, Nobu; Ueno, Saori; Miyano, Akira; Kamiyama, Rieko; Higuchi, Kazuhide
Abstract: Background: Malignant hilar biliary obstruction (MHBO) can be treated with bilateral self‐expandable metal stents (SEMS) deployed using side‐by‐side (SBS) or stent‐in‐stent (SIS) techniques. Moving cell stents (MCS) are a novel type of SEMS. The present study evaluated the technical feasibility of treating MHBO using bilateral novel uncovered SEMS to insert an SIS technique without dilating the mesh of a first stent within a single session. Method: We retrospectively assessed patients who were complicated with obstructive jaundice due to MHBO between August and December 2018. Technical success was defined as the deployment of a bilateral MCS into two or more biliary tracts using SIS technique without a dilation device. Results: The present study analyzed data from 23 consecutive patients who were complicated with MHBO. Bilateral SIS technique with MCS was deployed in 22 (95.6%) of the 23 patients without dilating the mesh of the first stent. Multiple guidewire insertion failed in one patient with Bismuth‐type IV. The median procedural duration was 33.6 min. Time to recurrent biliary obstruction was 230 days. Severe adverse events were not seen in any patients. Conclusion: In conclusion, uncovered moving cell SEMS might facilitate bilateral stent deployment using SIS technique. Abstract : Highlight Ogura and colleagues evaluated the technical feasibility of treating malignant hilar biliary obstruction with bilateral moving cell stents using a stent‐in‐stent technique without dilating the mesh of the first stent within a single session. Bilateral stent deployment was achieved successfully with this technique in 22 of the 23 patients studied.